Health-enhancing holidays challenges in expanding medical tourism in the Philippines - Picazo, Oscar F. (2013)
Medical tourism is poised to continue growing globally in the next few years due to combined economic, demographic, epidemiological, communication, and transport trends. While the Philippines offers better prices than its Asian competitors in surgical procedures, it continues to get a minuscule share of the medical tourism market. Why? What needs to be done to change this status?

This Policy Note provides a comprehensive view of the industry and discusses the global market demand and the drivers of growth. It then tries to understand the domestic industry by (a) exploring its demand and supply aspects, (b) undertaking an industry benchmarking exercise, and (c) examining strengths, weaknesses, opportunities, and threats.
Keywords: Medical tourism